Increase in cervical cancer mortality in Spain, 1951-1991. Issue 7 (1st July 1999) - Llorca, J; Prieto, M D; Delgado-Rodríguez, M
Abstract : BACKGROUND: The trend in cervical cancer mortality in Spain from 1951 to 1991 is examined. METHODS: Analysis of national mortality statistics calculating age standardised mortality rates and an age-period cohort analysis. A fit to the Gompertz function was made to estimate the influence of the environmental factors on the mortality rates evolution. MAIN RESULTS: The age standardised mortality rate in Spain is lower than in other developed countries (USA or Estonia) and equal to Norwegian and Finland rates; but whereas in these countries the trend is to decrease, the Spanish rate has increased during this period, because of a cohort effect. A misclassification bias could be responsible for the trend in women aged 40 and older but the increasing trend in younger women could not be interpreted as espurious. The Gompertzian analysis suggests an increase in environmental factors causing cervical cancer. CONCLUSIONS: Cervical cancer mortality rates are increasing in Spain because of environmental factors.